Elements of the set of diagrams of binary systems - L. А. Serafimov; А. V. Frolkova; V. V. Illarionov (Тонкие химические технологии, 2010)
All the possible elements of the set of binary systems (ideal, zeotropic, mono-, bi-, triazeotropic, homo- and heterogeneous) were explored. The overall amount of the possible types of diagrams of binary systems was calculated.